2016
DOI: 10.1101/069955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidative DNA damage is epigenetic by regulating gene transcription via base excision repair

Abstract: Reactive oxygen species (ROS) have emerged as important cellular signaling agents for survival. Herein, we demonstrate that ROS-mediated oxidation of DNA to yield 8-oxo-7,8dihydroguanine (OG) in gene promoters is a signaling agent for gene activation. Enhanced gene expression occurs when OG is formed in guanine-rich, potential G-quadruplex sequences (PQS) in promoter coding strands to initiate base excision repair (BER) by 8-oxoguanine DNA glycosylase (OGG1) yielding an abasic site (AP). The AP enables melting… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
156
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(164 citation statements)
references
References 35 publications
7
156
1
Order By: Relevance
“…Supporting this view is the fact that Fleming et al also provide a more comprehensive mechanistic explanation for the DNA oxidation and BER-dependent transcriptional activation reported in several cellular studies (4,10,11,21). In each case, the target gene investigated turned out to contain a PQS in its promoter (8).…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Supporting this view is the fact that Fleming et al also provide a more comprehensive mechanistic explanation for the DNA oxidation and BER-dependent transcriptional activation reported in several cellular studies (4,10,11,21). In each case, the target gene investigated turned out to contain a PQS in its promoter (8).…”
mentioning
confidence: 51%
“…As shown by the Barton group (22), redox electrons can "tunnel" through the pi-stacked bases of intact DNA duplex over distances of more than 200 Å. Intriguingly, the exits from such "tunnels" are often tracks of guanines, with the 5′-most guanine in a G track being most susceptible to oxidation (22). This mechanism may allow, at least initially, the focusing of a diffuse oxidative insult to select guanines in PQS in the genome, which, in light of the Fleming et al study (8), could initiate an oxidative stress-induced transcriptional response.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This provides a precedent that controlled DNA damage and repair can regulate active transcription. Other studies have also shown that site specific DNA damage can activate gene transcription (Ba et al 2014;Fleming, Ding, and Burrows 2017;Pan et al 2016;Pastukh et al 2015), though the mechanism through which damage occurs to specific points in the genome remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%